1999
DOI: 10.1063/1.124746
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of a coherent array of submicron SiO2 spheres (opal) embedded with Si nanoparticles

Abstract: The optical properties of a coherent array of 300 nm SiO2 spheres implanted with Si ions were shown to change nonlinearly with light intensity. These changes have been attributed to transverse confinement of the optical beam within the opal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Although the resulting structures were highly luminescent, implantation damage deformed the microspheres and the WGMs were not present in the PL spectra. Similarly severe implantation damage effects were observed in silicon-implanted silica microspheres for photonic crystal applications [14,15]. One recent study, also using the implantation method, did report oscillations in the PL spectrum, but the modes were weak [16].…”
Section: Introductionmentioning
confidence: 91%
“…Although the resulting structures were highly luminescent, implantation damage deformed the microspheres and the WGMs were not present in the PL spectra. Similarly severe implantation damage effects were observed in silicon-implanted silica microspheres for photonic crystal applications [14,15]. One recent study, also using the implantation method, did report oscillations in the PL spectrum, but the modes were weak [16].…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, nanocrystal-containing ordered arrays of microspheres may exhibit photonic crystal or optical microcavity effects. The first attempts to implant silicon into microspheres were not entirely successful due to the aggregation and melding of the microspheres into a semi-continuous layer [10,11]. More recently, we [13] and another group [12] have produced microsphere arrays that the survived the implantation and annealing processes.…”
Section: Silica Microspheresmentioning
confidence: 96%
“…The combination of lithography and light-ion implantation is a useful means for patterning magnetic films [9], and silica microspheres have been implanted with silicon in order to produce patterned photonic nanocrystal arrays [10,11]. Until recently, however, [12,13], the microspheres did not survive the ion implantation and annealing protocols as isolated entities, instead coagulating and ''melding'' into a semi-continuous implanted layer.…”
Section: Introductionmentioning
confidence: 99%
“…1͑c͒, we have concluded that the distribution of the Si nanoclusters within the matrix maintained a degree of the original opaline periodicity. 2,3 The structures have been shown to be highly nonlinear, 3,4 reaching index changes on the order of ͉␦n NL ͉Ͼ0.1 at femtosecond pulses at ϭ0.8 m and, and strongly dispersive. 5 Unlike Bragg fibers, 6 we employ here a transverse scheme, namely, the dispersion is achieved via transverse Bragg confinement 7 while maintaining nonresonance conditions along the propagation direction.…”
mentioning
confidence: 99%